1994
DOI: 10.1128/jb.176.24.7688-7693.1994
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitol promotes growth of Zymomonas mobilis in environments with high concentrations of sugar: evidence for a physiological function of glucose-fructose oxidoreductase in osmoprotection

Abstract: The gram-negative ethanologenic bacterium Zymomonas mobilis is able to grow in media containing high concentrations of glucose or other sugars. A novel compatible solute for bacteria, sorbitol, which enhances growth of Z. mobilis at glucose concentrations exceeding 0.83 M (15%), is described. Added sorbitol was accumulated intracellularly up to 1 M to counteract high external glucose concentrations (up to 1.66 M or 30o). Accumulation of sorbitol was triggered by a glucose upshift (e.g., from 0.33 to 1.27 M or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 36 publications
(40 reference statements)
1
68
0
4
Order By: Relevance
“…The localisation of GFOR in the periplasm of Z. mobilis was later observed by Loos et al (6) and confirmed by Aldrich et al (2). Afterwards, Loos et al (7) described the osmoprotective role of sorbitol for Z. mobilis, suggesting a physiological function of GFOR.…”
Section: Introductionmentioning
confidence: 55%
“…The localisation of GFOR in the periplasm of Z. mobilis was later observed by Loos et al (6) and confirmed by Aldrich et al (2). Afterwards, Loos et al (7) described the osmoprotective role of sorbitol for Z. mobilis, suggesting a physiological function of GFOR.…”
Section: Introductionmentioning
confidence: 55%
“…Loss et al (14) reported in their study that GFOR, present in the periplasm space of the bacterium, restrict sorbitol formation to conditions of osmotic stress. Because of its extraordinarily low affinity to fructose (Km 400 mM to 1M), sorbitol is formed at appreciable rates only when cells encounter high fructose concentrations.…”
Section: Sorbitol and Ethanol Production By Zymomonas Mobilis In Sucrmentioning
confidence: 99%
“…Polyols are also the major soluble carbohydrates in lichens (Dahlman et al, 2003), often found on the bark of trees, branches and leaves. Bacteria can also form and accumulate polyols (e.g., sorbitol) in order to overcome osmotic stress (Loos et al, 1994). Levoglucosan, with minor mannosan, galactosan and 1,6-anhydro-β-D-glucofuranose (levoglucosan isomer) are the primary thermal alteration products produced during biomass combustion of cellulose and hemicellulose and, therefore, are key tracers for smoke particulate matter from burning biomass .…”
Section: Introductionmentioning
confidence: 99%